Minimally Invasive Posterolateral Approach for Surgical Resection of Dumbbell Tumors of the Lumbar Spine - Kerimbayev, Talgat T.; Tuigynov, Zhandos M.; Aleinikov, Viktor G.; Urunbayev, Yermek A.; Kenzhegulov, Yergen N.; Baiskhanova, Dinara M.; Abishev, Nurzhan B.; Oshayev, Meirzhan S.; Solodovnikov, Makar P.; Akshulakov, Serik K. (Frontiers in Surgery, 2022)
Minimally invasive spine surgery (MISS) has many advantages over traditional open surgical procedures that can be conducted for the therapy of different diseases of the spine. MISS provide many prospective advantages such as, for example, small incisions, less damage to soft tissues, early activation of patients, and a shorter postoperative hospital stay. The aim of the study was to evaluate institutional experience with Dumbbell tumors and metastatic lesions of the lumbar spine and compare it with traditional open surgical resection of this type of tumors. Fourteen patients underwent the surgery with minimally invasive posterolateral approach in experimental group, and 10 patients of the control group were operated using the traditional open surgery procedure at the Department of spinal neurosurgery and pathology of peripheral nervous system of JSC “National Center for Neurosurgery.” The intraoperative neuro monitoring system (ISIS IOM System Compact, Inomed, Germany) was used in both groups. Sensory and motor evoked potentials were intraoperatively recorded. The present study was approved by the local Ethics Committee of the National Center for Neurosurgery. Patients signed informed consent before the surgical procedure. The experimental group included 14 patients, that underwent the surgery during the period from January 2020 till March 2021. And the control group included 10 patients that was operated from January 2018 to December 2019. The results of the treatment in both groups were assessed according to the generally accepted visual analog scale (VAS) and the Oswestry scales before, on the third day, and 3 months after the surgery. In experimental group, average reduction of the pain syndrome of 3.36 points (from 3 to 0 points) was observed in patients postoperatively according to the VAS 3 days, and of 4.0 points (from 2 to 0 points) 3 months after surgical procedures. Improvement by 23.86% (36–16%) was also observed using the Oswestry Disease Index (ODI) 3 days after the surgery, and then reduced to 21.00% (16–34%) in average in 3 months. All patients were revived 3 h after transfer to the specialist department. The average stay in the hospital was 6.5 (9–4) days in both groups. In control group, average reduction of the pain syndrome of 2.60 points (from 4 to 1 points) was observed postoperatively according to the VAS 3 days after the operation, and of 3.9 points (from 2 to 0 points) 3 months after the surgery. The ODI of patients was also improved by an average of 35.40% (50–20%) 3 days after the surgical procedure, and reduced to 24.20% (16–32%) in average 3 months after the surgery.